Analysis of the thermal behavior of rubber concrete at elevated temperatures based on the humidity levels: Numerical and mathematical modeling. (October 2022) - EL MARZAK, Mounir; KARIM SERROUKH, Hamza; BENAICHA, Mouhcine; HAFIDI ALAOUI, Adil; BURTSCHELL, Yves
Highlights: Analysis of the thermal behavior of rubber concrete. Development of numerical and mathematical models. Characterization of rubber concrete at very high temperature. Analysis of humidity effect on the thermal behavior of recycled concrete. Abstract: Reusing recycled tires in concrete instead of natural aggregates minimizes both the consumption of natural resources and the pollution that results from the disposal of used tires into the environment. However, there is a great need to study the thermal properties as well as the fire performance and accidental variations such as during a fire of this new concrete. In this research work, the concrete's thermal behavior made with rubber aggregates as a substitute for natural aggregates was evaluated. The substitution percentage varies from 0 to 30% with a step of 10%. The purpose of this study is to analyze the rubber aggregates' function and the humidity effect on the recycled concrete's thermal behavior, particularly the heat transfer time at high temperatures inside of the material (200, 400, 600, and 800 °C). To analyze the concrete behavior at extremely temperatures, this study was carried out using two approaches: an experimental method to characterize the concrete in its initial state and a numerical method according to two models: a numerical model using ANSYS software and a mathematical model, based on finite differences. The results obtained showed that the heat transfer times and the curves shapes of the temperature development as a function of time, resulting from these two approaches, are almost similar. This confirms the reliability of the mathematical model.